A new distributional record of Hippocampus kuda Bleeker, 1852 (Teleostei, Syngnathidae) from Saudi Arabia in the South-Central Red Sea - Charles, Santhosh; Short, Graham; Dimech, Mark (Zootaxa, 2024)
The common seahorse, Hippocampus kuda, is widely distributed throughout the Indo-Pacific region, occurring from East Africa to Hawaii, where it typically inhabits diverse ecosystems such as estuaries, lagoons, coastal zones, and seagrass beds. Despite its extensive geographic range, reports of its occurrence in the Red Sea remains limited, primarily restricted to the northern region of the Red Sea. Here, we report a new distributional record of H. kuda in Saudi Arabian waters within the south-central Red Sea. A single female specimen of H. kuda was collected through trawling conducted off the coast of Al Qunfudah at depths ranging from 15 to 20 meters. Morphological and molecular examination confirmed the identity of the specimen as H. kuda. The new record of H. kuda represents the second occurrence of this species in south-central Red Sea and expands its known distribution range 367 kilometers further south than the first reported record off Jeddah in 1838.